High resolution study of Hexades of H2MS; High Resolution Molecular Spectroscopy, HRMS 2018 - Zhang Fangce; Glushkov P. A. Petr Alekseevich; Belova A. S. Anastasiya Sergeevna; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Bauerekker Z. Zigurd; Sydow C. Christian; Maul C. Christof; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2018, 2018)
Title screen